Pharmacokinetic and bioequivalence study of Telzap® Plus fixed-dose combination compared with MikardisPlus® in healthy volunteers after single administration - A. L. Khokhlov; A. A. Khokhlov; A. E. Miroshnikov; O. V. Lebedeva; D. Yu. Grebenkin (LLC "Publisher OKI", 2023)
Introduction. A fixed dose combination of telmisartan and hydrochlorothiazide is indicated for treatment of in the treatment of arterial hypertension. The combination of these substances causes an additive effect that helps to reduce blood pressure. A bioequivalence study of Telzap® Plus compared with MikardisPlus® was conducted with 63 volunteers.Aim. The purpose of the bioequivalence trial was a comparative study of the pharmacokinetics and evidence of the bioequivalence of the fixed dose combination drug product Telzap® Plus (tablets 80 mg + 12,5 mg, Zentiva KS company, Czech Republic) compared with drug products MikardisPlus® (telmisartan+hydrochlorothiazide, tablets 80 mg + 12,5 mg, Boehringer Ingelheim Pharma GmbH & Co. KG, Germany) in healthy volunteers after a single administration under fasting.Materials and methods. To prove bioequivalence, an open label, comparative, randomized, crossover fourperiod replicate single-center clinical trial was conducted. The concentrations of hydrochlorothiazide and telmisartan in plasma samples were determined with a validated HPLC-MS/MS method. A pharmacokinetic and statistical analysis was performed and confidence intervals for the pharmacokinetic parameters Cmax and AUC0-72 were calculated.Results and discussion. It can be concluded that the studied formulations are bioequivalent in terms of pharmacokinetic parameters of hydrochlorothiazide and telmisartan. All 90 % confidence intervals for the estimated pharmacokinetic parameters of hydrochlorothiazide were in the range of 80-125 %, 90 % confidence intervals for telmisartan were within the bioequivalence range of 80-125 % for AUC0-72, and 79,30-126,11 % for Cmax.Conclusion. Thus, according to the criteria used in the study, the formulations are proved to be bioequivalent.